Impact of different hysterectomy techniques on postoperative clinical and sexual outcomes: A retrospective analysis in a tertiary center - Yusuf Başkıran; Gamze Karababa; Kazım Uçkan; İzzet Çeleğen (PLoS ONE, 2026)
Background Hysterectomy is a commonly performed gynecologic procedure; however, evidence regarding how different surgical techniques affect postoperative vaginal anatomy and sexual function remains inconsistent. This study aimed to evaluate postoperative vaginal length, female sexual function, male partner sexual function, and perioperative outcomes following total abdominal hysterectomy (TAH), total laparoscopic hysterectomy (TLH), and total vaginal hysterectomy (TVH) performed for benign gynecological indications. Methods In this retrospective cohort study, 466 women who underwent total hysterectomy between January 2020 and June 2023 at a tertiary referral center were included. Patients were grouped according to surgical technique: TAH, TLH, or TVH. Vaginal length measurements, Female Sexual Function Index (FSFI) scores, perioperative laboratory values, blood transfusion requirement, and postoperative complications were analyzed. Male partner sexual function was assessed using the International Index of Erectile Function-5 (IIEF-5) in a subset of patients. Multivariable linear and logistic regression analyses were performed to identify factors associated with postoperative outcomes. Estimated intraoperative blood loss was not consistently available in the retrospective database and could not be included in the transfusion model. Findings Of the 466 patients, 124 underwent TAH, 177 TLH, and 165 TVH. Preoperative vaginal length and FSFI scores were comparable across groups. Postoperative vaginal length differed significantly according to surgical technique, with the greatest reduction observed in the TLH group (p < 0.001). Postoperative female FSFI scores did not differ significantly among groups (p > 0.05). Among male partners with available data, IIEF-5 scores showed a statistically significant postoperative decline (mean ± SD: 14.87 ± 3.31 preoperatively vs. 14.10 ± 2.23 postoperatively; p < 0.001); however, this partner-related finding was exploratory. Blood transfusion was required in 12.0% of patients (95% CI, 9.4–15.3), and postoperative complications occurred in 8.2% (95% CI, 6.0–11.0). In multivariable analyses, lower preoperative hemoglobin levels were associated with a higher likelihood of blood transfusion. Longer operative time was associated with postoperative complications (OR per minute = 1.02; 95% CI, 1.01–1.03; p < 0.001), likely reflecting surgical complexity rather than a direct causal effect. Conclusions Hysterectomy technique was associated with differences in postoperative vaginal length, but these anatomical differences did not translate into significant differences in early postoperative female sexual function. Lower preoperative hemoglobin was associated with blood transfusion requirement, although the lack of estimated intraoperative blood loss data limits interpretation of transfusion-related findings. Longer operative time was associated with postoperative complications and may reflect greater surgical complexity. The observed decline in male partner IIEF-5 scores should be interpreted cautiously as an exploratory finding, and future prospective studies incorporating both patient- and partner-reported outcomes with longer follow-up are warranted.